O trabalho do repórter no processo de integração do impresso para o online no Diário Gaúcho, um jornal popular - Magalhães, Claiton dos Santos (2015)
Analyzing a case of convergence of printed to the online in a popular newspaper, the present work aims to discuss the new functions and tasks that are assigned to the report. The theories of news, the basic work of the reporter, and mobile technologies digital and its impact on productive routines of writing, serve as the basis for the study. The research, performed in the newspaper Diário Gaúcho, in Porto Alegre, proposes a discussion about the influences of webjournalism at work the reporter and in its daily function to capture the events of a reality.